Rare Neurological Manifestations of Scrub Typhus: Case Series from a Tertiary Care Centre in Kerala, India - NR Salini; T Sreena Sreekumar; Sudharmma Ramakrishnan; S Srikantan; Jacob Antony (Journal of Clinical and Diagnostic Research)
Scrub Typhus has emerged as an important cause of acute febrile illness in various parts of India over the last decade. Scrub Typhus is caused by Orientia tsutsugamushi, a rickettsia transmitted through the bites of infected chigger larvae. The neurological manifestations of Scrub Typhus can be highly variable. The most common neurological manifestation is meningoencephalitis. In addition to two cases of meningoencephalitis, hereby, the authors report three different rare neurological manifestations of Scrub Typhus that presented in the second week of illness. These included isolated sixth cranial nerve palsy, opsoclonus myoclonus, and transient Parkinsonism. All the patients responded to treatment with doxycycline, and authors had to use steroids for one patient with opsoclonus myoclonus. A characteristic eschar was seen in only one patient out of the five cases. Therefore, a high index of suspicion for Scrub Typhus is needed in patients presenting with acute febrile illness and Central Nervous System (CNS) manifestations in endemic areas.